CORRELATION OF SINGLE NUCLEOTIDE POLYMORPHISM OF THE INTERLEUKIN-27 GENE IN AUTOIMMUNE THYROID DISEASE. - Maryam H. I; Abdulkareem A. Al-Kazaz (The Iraqi Journal of Agricultural science)
The aim of this study was to investigate the association of IL-27 serum level and IL-27 gene SNP rs153109 with the risk and clinical features of the Iraqi patients with AITD. The blood samples were collected from 120 AITD patients and 60 healthy controls. Serum levels of interleukin-27 were assessed using ELISA kit. The study results showed a higher significant difference of IL-27 in sera of AITD patients compered to controls (p<0.001). The allele frequency and genotypes in the patient and control groups were determined using High-resolution melting (HRM) to detect the genetic variation in IL-27 gene SNP (rs153109). the result showed that CC and TC genotype of rs153109 had a statistically significant increased frequency in GD patients compared to controls (OR=19.4, P-value =0.0002), (OR=2.9, p-value =0.011). while the CC genotype of rs153109 was found to be more common in HT patients than control (OR = 6.8, value=0.017). In conclusion, the study suggested that genetic polymorphism of IL-27 gene rs153109 may be associated with AITD risk among Iraqi population.